Film “Tanda Tanya”: Suatu Gagasan Merealisasikan Multikulturalisme - Amirudin Amirudin (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2017)
This article is an essay that provides a cultural analysis of the movie "Tanda Tanya" by director HanungBramantyo with a linguistic anthropological perspective. Through the theory of Bourdieu (1992), the film is studied and dissected through symbolic capital that is played in every plot, scene, and picture contested in the film. On the basis of plot analysis, the film promotes an idea, multiculturalism which not only allowed at an idealistic level but also into a material practice.